Group Dynamics of Livestock based Self Help Groups (SHGs) - Chadda, Akshita; Jadoun, Y S; Kansal, SK; Singh, Jaswinder; Deshmukh, Bharti (Indian Journal of Extension Education, 2021)
The study was conducted in Ludhiana district of Punjab to observe the group dynamics of beneficiaries ofÂ livestock based Self Help Groups (SHGs) formed by different Self Help Group Promoting Institutions (SHGPIs).Â A total 120 SHG beneficiaries i.e., 40 beneficiaries from each SHGPIs were subjected to structured interview schedule. Majority (91.67%) of the beneficiaries were involved solely in dairy farming practices. Homogeneity in standard of living was one of the major factors promoting SHG formation as stated by 87.50 per cent NGOÂ promoted SHG beneficiaries and 75.00 per cent Government promoted SHG beneficiaries. Majority of the beneficiaries believed that they joined the group for â€˜family welfare & economic independenceâ€™. Decision making power, self confidence of the beneficiaries was reported improved after joining SHGs. Only 09.17 perÂ cent of the beneficiaries had attended training regarding animal husbandry practices. The main objective ofÂ group meetings was reported as â€˜collecting savingsâ€™ and â€˜inter-loaning among group beneficiariesâ€™ as keyÂ purpose for utilizing saving amount. Milk sale and savings were the major income generating activities amongÂ all the beneficiaries. The difference between group dynamics was found statistically significant among the beneficiaries of different SHGPIs (P<0.05). Beneficiaries of Dairy Co-operative were having better followed by beneficiaries of NGO and Government promoted SHGs. It has been inferred that the efficient functioning ofÂ SHGs depends upon a large number of factors such as trust among the beneficiaries, motivation to join SHGs, record keeping, freedom of participation, decision-making, leadership, face-to-face communication, groupÂ homogeneity and conflict management.